(3GdMOGFb GdhQOjI aj efGbH GdCFeI GdRHOjIs - (3MejO Hf CMeO GdnenMpqdj GdgeOGfqj, CHh YHO Gddg MSGe GdOjf, GdeYQha HGdbGVj GdTgjO,J (B652 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV YdjfG CfhGQ GdgOGjI s
(3GdLRA GdChd ai eLdO eCNhP HGdJUhjQ GdTeSi Yf GdfSNI GdNWjI ai SfI (B972 (3GdeNWhWI HecJHI dfOfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B83s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B325 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B114 s
Keywords: (3GdJGQjNs